Go - Life Enterprise: "Fruit Cutter Tumbler" / Muhammad Shakir Zakaria...[et.al] - Zakaria, Muhammad Shakir; Abd Razak, Radziah; Mohd Azmi, Nur Munirah; Syafiqul Hafiz, Mohamad; Rahim, Nurul Nadia (Faculty of Plantation and Agrotechnology, 2017)
GoLife Enterprise is a business partnership. The business address is at G-17, Jalan Plumbum, Seksyen 7, Shah Alam, Selangor Darul Ehsan. There are 5 shareholders that have cooperated and responsible in collecting some capitals to build this company. They are Muhammad Shakir Bin Zakaria as general manager, Radziah Abd Razak as administration manager, Nur Munirah binti Mohd Azmi as marketing manager, Mohamad Syafiqul Hafiz as operation manager and Nurul Nadia binti Rahim as financial manager.